Inovasi Pengabdian Masyarakat dalam Pencegahan dan Pendampingan Stunting di Desa Talakbroto, Kabupaten Boyolali - Marisa Alifaturrohmah; Ardilla Aulia Putri; Yanitama, Arka (Universitas Negeri Semarang, 2024)
Stunting is a condition that attacks toddlers by disrupting physical growth, brain development and nutritional development. Factors that cause stunting generally come from nutritional problems when the mother is pregnant. The aim of the service of the UNNES GIAT 6 Talakbroto Village Team is to prevent and provide assistance regarding stunting in toddlers and pregnant women who suffer from Chronic Energy Deficiency (CED). Dukuh Krambillit and Dukuh Talakbroto are two hamlets whose residents are at risk of stunting and pregnant women suffer from CED. This service uses the direct deployment method with the method of carrying out socialization and assistance to the service locations, namely Krambilsawit Hamlet and Talakbroto Hamlet, Talakbroto Village, Simo District, Boyolali Regency in two ways, namely: (1) Prevention of stunting through socialization with the theme